CGIAR Consultation Workshop with innovation ecosystem in Uzbekistan for sustainable agriculture and climate action - Menza, Gianpiero; Zaccari, Claudia (2022)
The Consultation Workshop was hosted by CGIAR centers ICARDA, IFPRI, IWMI, and the Alliance of Bioversity International and CIAT with the support of the CGIAR Accelerate for Impact Platform, and in collaboration with StartupFactory.